Escola de tempo integral: relato de uma experi??ncia na rede estadual de ensino de S??o Paulo - Babalim, Val??ria de Souza (2016)
In 2005, the State Department of Education of S??o Paulo established the Full-Time School project in some primary education schools. In 2012, a new project of the Department of Education, now called Integral Education Program - Full Time School is implemented, with new guidelines and also incorporating the high school. This research aims to understand teachers??? concept of integral education and how school work was affected by this change. Our central problem work can be broken down into two questions: how teachers understand the objectives, procedures, concepts and guidelines of Integral Education Program - Full Time School and what changes occurred (or not) in the pedagogical work of these teachers. Primary research sources were constituted of official documents that support the program and five interviews with teachers, two of whom are also full-time school coordinators. The objective was to obtain data on teachers??? training, their understanding of comprehensive education and their analysis of the educational work process after joining the program. Given the results of this research, we can say that the interviewed teachers follow the debate on comprehensive education, they observed considerable changes in pedagogical work in full-time schools and consider the project relevant for students.